High torque realization of the stepping over gait for a humanoid robot. Issue 4 (8th June 2020) - Bai, Keqiang; Luo, Yunzhi; Jiang, Guanwu; Jiang, Guoli; Guo, Li
Abstract : Purpose: This paper aims to propose a pulsing type joint servo driver-based obstacle surmounting method for a humanoid robot according to the whole-body dynamics model, which fully takes into account the relationship between the whole-body stability margin and instantaneous torque. Design/methodology/approach: First, the authors designed a new practical instantaneous large torque strategy for a pulsing type joint servo driver by modeling the whole-body dynamics of the humanoid robot. The work also considered joint angle planning based on the dynamic model for crossing obstacles. Second, in the simulation and experimentation, the instantaneous torque of the driver is used to realize successful crossing of obstacles by the humanoid robot. This verifies the correctness of the whole-body dynamics model and the feasibility of the method for crossing obstacles. Findings: The experimental data and results are described and analyzed, showing that the proposed method is feasible and effective through simulation and implementation. Originality/value: The main contribution is the humanoid robot's actuation control technology and humanoid action realization, which could be used for squatting and moving heavy objects to help a humanoid robot adapt effectively.